Studi literatur aspek manajemen dan strategi transisi belajar dari sekolah menengah ke perguruan tinggi - Arifin, Arifin; Sarlin, Muhammad; Kartili, Sukri; Rahman, Yurni; Haris, Ikhfan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to describe management aspects and learning transition strategies from high school to college. This research uses library study or content analysis methods. The results of this study indicate that managing a successful transition from high school to college is critical to students' academic success, especially in the first year. Various studies show that many students are less prepared to study at university and experience obstacles, especially in the aspect of learning adjustment. The gap not only occurs in the secondary school system which does not fully prepare its students to enter college, but colleges also do not have the equipment to accommodate students from secondary schools. To make the transition from high school to college, students need to make adjustments and be supported by the people and systems in their environment. From the aspect of students who will become students, they need to prepare three separate stages in the transition process, namely: separation/separation, transition/transition and merger/merger. From the aspect of higher education, it is necessary to prepare strategies, programs and services to facilitate the transition for students who will enter college. This article reviews the results of a collection of literature regarding management and successful strategies implemented in various countries in facilitating learning from high school to university. The purpose of this literature review is to produce recommendations and considerations that can be used as guidelines for students, parents and universities involved in transition to manage the transition well and successfully.